Effectiveness of an mHealth-Based Electronic Decision Support System for Integrated Management of Chronic Conditions in Primary Care: The mWellcare Cluster-Randomized Controlled Trial. Issue 3 (15th January 2019) - Prabhakaran, Dorairaj; Jha, Dilip; Prieto-Merino, David; Roy, Ambuj; Singh, Kavita; Ajay, Vamadevan S.; Jindal, Devraj; Gupta, Priti; Kondal, Dimple; Goenka, Shifalika; Jacob, Pramod; Singh, Rekha; et al.
Abstract : Background: The burden of noncommunicable diseases and their risk factors has rapidly increased worldwide, including in India. Innovative management strategies with electronic decision support and task sharing have been assessed for hypertension, diabetes mellitus, and depression individually, but an integrated package for multiple chronic condition management in primary care has not been evaluated. Methods: In a prospective, multicenter, open-label, cluster-randomized controlled trial involving 40 community health centers, using hypertension and diabetes mellitus as entry points, we evaluated the effectiveness of mWellcare, an mHealth system consisting of electronic health record storage and an electronic decision support for the integrated management of 5 chronic conditions (hypertension, diabetes mellitus, current tobacco and alcohol use, and depression) versus enhanced usual care among patients with hypertension and diabetes mellitus in India. At trial end (12-month follow-up), using intention-to-treat analysis, we examined the mean difference between arms in change in systolic blood pressure and glycated hemoglobin as primary outcomes and fasting blood glucose, total cholesterol, predicted 10-year risk of cardiovascular disease, depression score, and proportions reporting tobacco and alcohol use as secondary outcomes. Mixed-effects regression models were used to account for clustering and other confounding variables. Results: Among 3698 enrolled participants across 40 clusters (mean age, 55.1 years; SD, 11 years; 55.2% men), 3324 completed the trial. There was no evidence of difference between the 2 arms for systolic blood pressure (Δ=−0.98; 95% CI, −4.64 to 2.67) and glycated hemoglobin (Δ=0.11; 95% CI, −0.24 to 0.45) even after adjustment of several key variables (adjusted differences for systolic blood pressure: – 0.31 [95% CI, −3.91 to 3.29]; for glycated hemoglobin: 0.08 [95% CI, −0.27 to 0.44]). The mean within-group changes in systolic blood pressure in mWellcare and enhanced usual care were −13.65 mm Hg versus −12.66 mm Hg, respectively, and for glycated hemoglobin were −0.48% and −0.58%, respectively. Similarly, there were no differences in the changes between the 2 groups for tobacco and alcohol use or other secondary outcomes. Conclusions: We did not find an incremental benefit of mWellcare over enhanced usual care in the management of the chronic conditions studied. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02480062. Abstract : Supplemental Digital Content is available in the text.